Japanese Merchants Diaspora in the 17th Century into Southeast Asia - Riza Afita Surya (IZUMI, 2021)
This study aimed to investigate the Japanese Diaspora in the 17th century into Southeast Asia. This article   discussed critically the  motives, process, and the effect of Japanese diaspora in the Southeast Asia. Reseacher utilized historical method with descriptive approach. The process being performed namely heuristics, critism, interpretation, and historiography. Japanese history regarding abroad migration is an interesting issue between scholars who studied migration, anthropology, and minority studies over the decades. Edo period in Japan is one of the most studied field for many scholars for Japanese studies, since it shaped the characteristic of Japanese culture until today. Trade of Japan is significant part of its economical development since the pre-modern era. In the 17th century, Japan established a solid trade network with Southeast Asia regions, namely Siam, Malacca,  Cambodia, Vietnam and Manila. The emerge of maritime trade with Southeast Asia encouraged Japanese merchants to travel and create settlements in some regions. The Japanese diaspora was encouraged with vermillion seal trade which allowed them to do journey overseas and settled in some places, which eventually increased the number of Japanese merchants in the Southeast Asia. However, after the Sakoku policy there was restriction of trade relation ehich prohibited overseas maritime trade, except for China and Dutch. Sakoku policy caused Japanese merchants who stayed overseas could not return for many years, then they settled themselves as Japanese communities known as Nihon Machi in some places within Southeast Asia. History of early modern Japan between the 16th and 19th century provides a broader narratives of global history as it was surrounded by intense global interaction.